PENYUTRADARAAN DOKUMENTER “LELABUH ROSO ING MERAPI” DENGAN GAYA EXPOSITORY - Beta Santika; Widyaningtyas Virgo K.; Ghalif Putra S. (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACTThe finished work "Lelabuh Roso Ing Merapi" was made into an audio visualwork after undergoing a long process from pre-production to post-production which tookmonths. In the production, the writer acts as a director who regulates all kinds ofconditions for making the work, starting from the idea being developed until the end ofthe work editing process. The director is not only responsible as a leader in the productionof a work, but also as a technical advisor for both camera and writing, as a developer ofideas which are then maximized with the script writer, and observing how the work can bedisplayed in the desired media, in this case YouTube. The director as the writer, uses anexpository style, combined with an observational directing style, with the hope ofstrengthening the naturalness of the visuals, and also aims to show the other side of theoffering itself. The work that has been created with a duration of 24 minutes is inaccordance with the provisions applicable by the academic authorities. It is hoped thateverything from this work can provide new information, so that it can indirectly be usedas knowledge for the general public, from young to old, so that they know more about theother side of the cultures or traditions that were once upheld by their ancestors, who nowit is still preserved for the people who believe and believe in it. And it is hoped that theaudience will also be able to enjoy this work which has been presented through thetheories used, starting from directing style, writing techniques, and also the variety ofshots taken and displayed in the work and report.Keywords: Lelabuh Roso Ing Merapi, Labuhan Merapi, Director, Expository, Documentary.